SISTEM PAKAR BAWANG DAYAK SEBAGAI OBAT ALTERNATIF - Widians, Joan Angelina; Puspitasari, Novianti; Kurniawan, Tri Basuki (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2021)
The medicinal plants that have been developed especially in East Kalimantan is the dayak onion (Eleutherine palmifolia (L.) Merr). The Dayak onion herb has long been used by the Dayak tribe as an alternative medicine. Information of the possibility of people affected by the disease and how to process Dayak onion ingredients , an expert system needs to build that is able to diagnose the disease and how to process Dayak onion ingredients. The result of this research is an expert system with Certainty Factor that helps the general public in early diagnosis of ten diseases and provides alternative treatment solutions and ways of Dayak onion as an alternative medicine.